Vulvar Lichen Sclerosus. Issue 2 (April 2015) - Murina, Filippo; Rehman, Subhia; Di Francesco, Stefania; Mantegazza, Valeria; Felice, Raffaele; Bianco, Vanda
<x xml:space="preserve">Abstract</x> Objective To compare the efficacy of the short-term application of clobetasol propionate 0.05% (CLB) and mometasone furoate 0.05% (MMF) in the treatment of vulvar lichen sclerosus (VLS). Study Design This study was a retrospective review of 96 women who were diagnosed with lichen sclerosus with a follow-up of at least 1 year. Of these 96 women, 47 were treated with the topical application of CLB and 49 were treated with the topical application of MMF. All patients received treatment for 8 weeks. The drug was administered once daily for 4 weeks and then twice weekly for another 4 weeks in combination with a moisturizing cream that was continued as maintenance therapy. Subsequently, a topical steroid was applied on an as-needed basis if symptoms recurred. Follow-up visits were scheduled at 3, 6, and 12 months. The primary endpoint was the clinical response of the patients. Results A mean of 77.3% of the patients were defined as responders at the 12-month observation, without any significant difference between the 2 treatment groups (CLB mean 73% vs MMF mean 81.6%, p = .2). A pronounced improvement in itching was observed after 3 months of treatment in the MMF group (p = .04), whereas the other symptoms were not significantly different between the 2 groups. Conclusions This study indicates that CLB 0.05% and MMF 0.1% in a short protocol regimen are effective, safe, and reliable treatments for VLS, with no significant difference between the 2 steroids in their efficacy. However, a moisturizing cream should be an integral part of the treatment.